2014
DOI: 10.1017/s0317167100018540
|View full text |Cite
|
Sign up to set email alerts
|

A Chinese Patient with Pusher Syndrome and Unilateral Spatial Neglect Syndrome

Abstract: Objective:To observe clinical manifestations, behavioral characteristics, and effects of rehabilitation on a patient with pusher syndrome and unilateral spatial neglect caused by right thalamic hemorrhage.Methods:Assessment of pusher syndrome was made by the Scale for Contraversive pushing (SCP), and unilateral spatial neglect syndrome was diagnosed using line cancellation, letter and star cancellation, line bisection tests and copy and continuation of graphic sequence test. Behavioral therapy, occupational th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
1
0
2
Order By: Relevance
“…Foram identificados 9 artigos científicos, publicados entre 2004 e 2021, 3 provenientes da China (13)(14)(15) , 2 da Alemanha (16,17) , 1 dos Estados Unidos (10) , 1 da Coreia do Sul (18) , 1 de Taiwan (19) e 1 de Itália (20) . A maior parte destes artigos recorreu à metodologia estudo de caso (6) (10,13,15,16,18,20) e 2 deles são experimentais (14,19) , abrangendo 72 pessoas com síndrome de pusher. Um dos artigos não aborda o tipo de metodologia implementada (17) .…”
Section: Resultsunclassified
“…Foram identificados 9 artigos científicos, publicados entre 2004 e 2021, 3 provenientes da China (13)(14)(15) , 2 da Alemanha (16,17) , 1 dos Estados Unidos (10) , 1 da Coreia do Sul (18) , 1 de Taiwan (19) e 1 de Itália (20) . A maior parte destes artigos recorreu à metodologia estudo de caso (6) (10,13,15,16,18,20) e 2 deles são experimentais (14,19) , abrangendo 72 pessoas com síndrome de pusher. Um dos artigos não aborda o tipo de metodologia implementada (17) .…”
Section: Resultsunclassified
“…In a retrospective analysis of a large sample, Dai et al ( 10 ) found that all patients with PS had USN and 97% of those with USN had PS. Chen et al ( 26 ) reported that PS correlated with USN in approximately 80% of patients with right hemispheric injury.…”
Section: Discussionmentioning
confidence: 99%
“…Причем чаще причиной синдрома отталкивания становится поражение правого полушария, что дает основания предполагать, что центральные отделы вестибулярной системы именно правого полушария главным образом отвечают за восприятие вертикали [20]. Другое объяснение связывает синдром отталкивания с односторонним пространственным игнорированием [23,24].…”
Section: вестибулярные синдромы высшего уровняunclassified